PERLINDUNGAN HUKUM BAGI PEREMPUAN DALAM PRAKTEK PERKAWINAN SIRI DI KEPULAUAN KANGEAN - Adib, Ahmad Akhil (EGALITA, 2023)
Marriage registration is an official procedure in order to obtain legal certainty in the husband-wife bond as in Article 2 Paragraph (2) of Law Number 1 of 1974 concerning Marriage explains that every marriage is recorded according to the applicable laws and regulations. Therefore, a valid marriage must be proven by a marriage certificate issued by the Religious Affairs Office. The purpose of this research is to analyze the status of women (wives) in unregistered marriages that occur in the Kangean Islands community based on Law Number 1 of 1974 concerning Marriage and in the Compilation of Islamic Law that the marriage is a marriage that is not recognized by the state, therefore the marriage is not have legal certainty and protection. The research method used is normative through a statutory approach with the addition of data from the Kangean Religious Court. With the many cases of unregistered marriages in the Kangean Islands, the Kangean Religious Court as a legal institution provides a solution by determining (itsbat) the marriage as a valid marriage and has legality from the State as explained in the Compilation of Islamic Law Article 7 Paragraph (2) that in the case of marriage cannot be proven by a marriage certificate, the marriage certificate can be submitted to the Religious Court.